Aplikasi Yayasan Pendidikan Surau Minang Berbasis Digital bagi Wali Murid di SDIT Padang Islamic School - Mufti, Zaki Aulia; Kustati, Martin; Amelia, Rezki; Kurnia, Asraf (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2024)
This service aims to describe the use of the digital-based YPSM (Yayasan Pendidikan Surau Minang) application at SDIT Padang Islamic School as an effort to improve the efficiency and effectiveness of the school administration system. The method used in this service is service learning. The learning procedure in experiential learning consists of 4 stages, namely; real experience stage, reflection observation stage, conceptualization stage, and implementation stage. This includes ensuring optimal understanding for all participants, consisting of student guardians and teachers. The results of this service showed that the training provided was able to improve the understanding and skills of the Student Guardians in operating the YPSM (Yayasan Pendidikan Surau Minang) application. With this socialization, it is hoped that the implementation of this application can accelerate access to information, increase administrative transparency, and strengthen communication between the school and parents. With this training, it is hoped that schools can be better prepared to adopt digital technology to support a more modern and efficient education system